2020
DOI: 10.1038/s41467-020-15534-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal refinement of signal flow through association cortex during learning

Abstract: Association areas in neocortex encode novel stimulus-outcome relationships, but the principles of their engagement during task learning remain elusive. Using chronic wide-field calcium imaging, we reveal two phases of spatiotemporal refinement of layer 2/3 cortical activity in mice learning whisker-based texture discrimination in the dark. Even before mice reach learning threshold, association cortex-including rostro-lateral (RL), posteromedial (PM), and retrosplenial dorsal (RD) areas-is generally suppressed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 74 publications
4
81
0
Order By: Relevance
“…More recently, the advent of genetically encoded calcium 1 and voltage indicators 2,3 , along with transgenic approaches for broadly expressing these indicators in the brain in a cell-type specific fashion 4,5 has enabled mesoscale imaging of multiple cortical regions simultaneously [6][7][8] . These studies have revealed how neural activity across multiple regions of the cortex are coordinated in a variety of brain states and behaviors [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the advent of genetically encoded calcium 1 and voltage indicators 2,3 , along with transgenic approaches for broadly expressing these indicators in the brain in a cell-type specific fashion 4,5 has enabled mesoscale imaging of multiple cortical regions simultaneously [6][7][8] . These studies have revealed how neural activity across multiple regions of the cortex are coordinated in a variety of brain states and behaviors [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…The concentrating effect of scattering is lost when angles at the brain surface are randomized, such as by overlying skull. In mouse, widefield imaging is often performed through intact skull ( Mohajerani et al, 2013 ; Silasi et al, 2016 ; Allen et al, 2017 ; Makino et al, 2017 ; Gilad and Helmchen, 2020 ; Valley et al, 2020 ). Mouse skull is ~150–300 µm thick and transparent but strongly scattering ( Soleimanzad et al, 2017 ; Wang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…forelimb movement, nose twitching, whisking, licking etc. ), which were recently found to have substantial impact on neuronal activity in different brain areas ( Gilad et al, 2018 ; Gilad and Helmchen, 2020 ; Musall et al, 2019 ; Stringer et al, 2019 ). As mentioned above, we continuously monitored the body movements of the mouse throughout the experiment ( Figures 1A and 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Learning, the process of acquiring new knowledge through experience, is known to involve disparate brain areas, and particularly the cortex. For example, learning to discriminate between different sensory stimuli leads to changes in the respective primary sensory areas ( Blake et al, 2002 ; Chen et al, 2015 ; Driscoll et al, 2017 ; Gilad and Helmchen, 2020 ; Jurjut et al, 2017 ; Komiyama et al, 2010 ; Li et al, 2008 ; Makino and Komiyama, 2015 ; Poort et al, 2015 ; Yan et al, 2014 ). Cortical neural responses have often been shown to strengthen after learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation